Relationship between pulp pathosis and NK cell activity - Viloria, Iluminada (The Journal of the Philippine Dental Association)
Pulpal and periapical generally show inflammatory reaction to any kind of irritants. These endodontic pathoses might affect the systemic conditions, especially the immune system. However, there is little information about the effect of pulpal and periradicular diseases to immunological deficiency. The aim of the present study was to investigate the relationship between the pulpal and periradicular pathoses and immunosuppression. The effect of chemically induced endodontic lesions on the natural killer (NK) cell activity in blood was analyzed. Histopathological findings together with immunological changes clearly showed that pulp tissue dressed with arsenic trioxide significantly suppressed the NK cell activity until 7 days postoperatively. These findings provide the first evidence that diseases originating from the pulp may alter the function of killer lymphocytes as evidenced by the suppression of NK cell activity. Teeth requiring endodontic treatment should be addressed properly to promote health life and maintain good immune system.